UPLC–QTOF-MS-Based Plasma Lipidomic Profiling Reveals Biomarkers for Inflammatory Bowel Disease Diagnosis - Guan, Su; Jia, Bingjie; Chao, Kang; Zhu, Xia; Tang, Jian; Li, Miao; Wu, Lvying; Xing, Lei; Liu, Kun; Zhang, Lei; Wang, Xueding; Gao, Xiang; et al. (Journal of proteome research, 2020)
Identification of new biomarkers may help in the early diagnosis of inflammatory bowel disease (IBD). In this study, ultrahigh-performance liquid chromatography equipped with quadrupole time-of-flight mass spectrometry (UPLC–QTOF-MS) was used to analyze the untargeted lipidomics and compare plasma lipid profiles between IBD patients and control subjects. The principal component analysis and partial least-squares-discriminant analysis were carried out to distinguish IBD patients from control subjects. Using univariate and multivariate analysis, 55 significantly different metabolites from five lipid classes, fatty acyls (n = 19), glycerophospholipids (n = 5), prenol lipids (n = 10), sphingolipids (n = 2), and sterol lipids (n = 19) were identified. Forty-four of the 55 metabolites were analyzed by receiver operating characteristic (ROC) curve and area under curve (AUC) of >0.80. After validation in an independent cohort, IBD patients were differentiated from the control subjects by significantly altered plasma level of palmitic acid, 7alpha, 25-dihydroxycholesterol, 20-hydroxyeicosatetraenoic (HETE)-d6, (+/−)5,6-epoxy-eicosatrienoic acid (EpETrE), docosahexaenoic acid (DHA), 9-heptadecylenic acid, lactucaxanthin, α-carotene, traumatic acid, and neoquassin with both sensitivity and specificity above 80%. Pathway analysis suggested that IBD dysregulation was related to the biosynthesis of primary bile acid, the metabolism of arachidonic acid, the metabolism of sphingolipid, fatty acid elongation, and glycerophospholipid metabolism. Our results suggest that the lipidomic profiling of patients plasma could be a potential method for IBD diagnosis.